Business data communications and networking a research perspective - Gutierrez, Jairo, 1960- (Idea Group Pub., 2007)
"This book addresses key issues for businesses utilizing data communications and the increasing importance of networking technologies in business; it covers a series of technical advances in the field while highlighting their respective contributions to business or organizational goals, and centers on the issues of network-based applications, mobility, wireless networks and network security"--Provided by publisher.